Work and health care in Milan, 1864-1874 - Porro, Alessandro; Lorusso, Lorenzo; Falconi, Bruno; Franchini, Antonia Francesca (La Medicina del Lavoro, 2017)
In 1864 in Milan, Giovanni Rosmini (1832-1896) opened an ophthalmic dispensary for workers. In 1874 this dispensary was transformed into the first ophthalmic hospital of the city. This hospital still exists today. The authors analyze a document that belonged to the lawyer Enrico Rosmini (1828-1898), brother of Giovanni, which helps to piece together the early years of the dispensary, where about 4,000 surgeries were carried out in the first four years of activity. This historical document is valuable as it sheds light on one of the first healthcare institution for workers in Milan.